Partitioning effects and corrosion characteristics of oxyapatite glass-ceramic wasteforms sequestering rare-earth elements - Miae Kim; Jaehyuk Kang; Jang-Hee Yoon; Sang-Geul Lee; Wooyong Um; Hyun Gyu Kim (Nuclear Engineering and Technology, 2022)
Oxyapatite[Ca2Nd8(SiO4)6O2] glass-ceramics have been suggested as wasteforms for the immobilisation of rare-earth radioactive nuclides because of their high waste-loading capability and good chemical durability. In particular, a partitioning effect is predicted to contribute to an enhancement of corrosion resistance in glass-ceramics compared with that of conjugate glasses of the same composition. Because rare-earths are inherently insoluble nuclides, detection of changes in corrosion behavior between glass-ceramics and conjugate glasses under normal conditions is not easy. In this study, therefore, we revealed the partitioning effect by exposing glass-ceramics and glasses to solution of pH 2, 7 and 10 at 90 °C for 20 d. In addition, we proposed the corrosion mechanism for oxyapatite glass-ceramics under various corrosion conditions. Especially, the glassy phase dissolved first, followed by the oxyapatite phase during pH 7 corrosion.